Modelling the central bank repo rate in a dynamic general equilibrium framework - Leão, E. R. (2007)
The present paper adds a central bank to an existing general equilibrium model with banking sector. In our model, the central bank lends reserves to commercial banks and charges its repo interest rate. We obtain the usual result of flexible price models that expansionary monetary policy has a negligible effect on real variables such as output, consumption and investment expenditure. However, the composition of total investment is significantly altered as investment by banks increases at the expense of investment by nonbank firms. This result is a consequence of our explicit modelling of the central bank repo rate.